2021
DOI: 10.52562/injoes.v1i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Estimasi Tingkat Bahaya Erosi dengan Menggunakan Metode USLE Pada Daerah Aliran Sungai (DAS) Amandit

Abstract: Abstrak: Erosi tanah menjadi semakin meningkat setiap tahun yang disebabkan oleh terjadinya peningkatan kerusakan lahan. Daerah Aliran Sungai (DAS) Amandit mengalami kerusakan lahan yang ditandai dengan luasnya lahan kritis pada DAS tersebut yang akan berpengaruh pada tingginya tingkat bahaya erosi pada DAS tersebut. Penelitian ini bertujuan untuk menganalisis tingkat bahaya erosi yang terjadi pada Daerah Aliran Sungai (DAS) Amandit. Penelitian ini menggunakan peta bentuklahan sebagai dasar pengambilan sampel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most considerable erosion rate in the Padang Batung Sub-district area is 1895.69 tons/ha/yr. In 2020 the total erosion rate in the Padang Batung Sub-district area studied by Safitri (2021) was 932,933 tons/ha/yr, so it can be seen that the erosion rate in the Padang Batung Sub-district area has increased. This change in value results from the high rain intensity, causing the erosivity index to increase.…”
Section: Calculation Of Erosion Rate In Padang Batung Sub-districtmentioning
confidence: 99%
See 1 more Smart Citation
“…The most considerable erosion rate in the Padang Batung Sub-district area is 1895.69 tons/ha/yr. In 2020 the total erosion rate in the Padang Batung Sub-district area studied by Safitri (2021) was 932,933 tons/ha/yr, so it can be seen that the erosion rate in the Padang Batung Sub-district area has increased. This change in value results from the high rain intensity, causing the erosivity index to increase.…”
Section: Calculation Of Erosion Rate In Padang Batung Sub-districtmentioning
confidence: 99%
“…The critical land area in Hulu Sungai Selatan Regency has an area of 33,263 ha, which is incorporated from several categories of critical land, including the critical land category covering an area of 29,701 ha and very critical land covering an area of 3,562 ha, which is spread in almost every Sub-district in Hulu Sungai Selatan Regency (BPDASHL Barito, 2018). Padang Batung Sub-district is located in Hulu Sungai Selatan Regency, South Kalimantan Province, with natural conditions in the form of plains-hills-mountains with rather steep slopes (15-30%) with structural and denudational landforms (Safitri et al, 2021). Land use in communities in Padang Batung Sub-district is in a location with a relatively steep slope.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on the potential for erosion, including: Research conducted in East Java shows that the USLE method can be used to predict erosion quickly over a large area [1]. The dominant factors that cause the level of erosion hazard in the Amandit Watershed included in the heavy-to-very heavy classification are the slope, high erodibility value, and land cover [2]. The results of the research in the Panasen sub-watershed of Minahasa Regency showed that not all soil that was lifted from the ground surface through the process of erosion, entered the lake and became sediment [3].…”
Section: Introductionmentioning
confidence: 99%